Short-term outcomes after long inverted versus short standard biliopancreatic limb in Roux-en-Y gastric bypass - Morfin Vela, Cuauhtemoc; Spaventa Ibarrola, Antonio G.; Lopez, Carlos Zerrweck; Rodriguez Gonzalez, Arturo A.; Vargas Sahagun, Cesar M.; Benavides Zavala, Tomas E. (International Journal of Research in Medical Sciences, 2022)
Background: Obesity is a public health issue that affects the entire world and it is rising. Roux-en-Y gastric bypass is one of the most common bariatric procedures and it can reach a significant and sustained excess weight loss and efficient comorbidity control. The main objective was to compare short-term outcomes between standard versus long biliopancreatic limb gastric bypass patients. Methods: it was a retrospective, comparative, descriptive, single-center study. We evaluated obese patients that underwent a laparoscopic Roux-en-Y gastric bypass with standard or long biliopancreatic limb in Centro Medico ABC, Mexico City, and compared general demographics, weight loss, excess weight loss, comorbidities and quality of life. Results: Of 50 patients analyzed, 24 were in the standard gastric bypass (S-GB) and 26 in the long biliopancreatic limb (LBPL-GB). Mean weight loss in the S-GB group was 33.1±12.1 kg and in the LBPL-GB was 40.2±12.6 kg with a difference of 7.1 kg. The percentage of excess weight loss (%EWL) was 72.5±14% in S-GB and 72.9±19% in LBPL-GB, with a difference of 0.4% in the 12 months of follow-up. There was a complete reduction of hypoglycemic drugs in 80% in the S-GB group and 100% in the LBPL-GB group. Conclusions: With this modification of the technique, we achieved important outcomes in regard of comorbidities, without affecting drastically weight loss or the EWL. This procedure is safe and feasible.